Charcot-Marie-Tooth disease: A case report initially manifested by bilateral vocal cord paralysis - Seyed Hossein Mirlohi; Sanaz Tajfirooz; Mitra Rouhi (Respiratory Medicine Case Reports)
Charcot-Marie-Tooth is an inherited disorder involving multiple genes, causing progressive nerve damage affecting sensation and movement. The complexity of the condition often leads to various possible diagnoses along with neuropathic diseases, sometimes resulting in significant delays in diagnosis and treatment. Thorough clinical examinations, suspicion based on symptoms, electromyography, nerve conduction tests, and specific genomic testing can expedite diagnosis. Here, we will introduce a case of Charcot-Marie-Tooth disorder, initially presenting with stridor and hoarseness due to vocal cord paralysis, later progressing to atrophy and deformity of the limbs. Diagnosis was confirmed through whole genome sequencing, revealing mutations in genes associated with the disorder.